Invertible architectures from amphiphilic polyesters. - Peukert, Wolfgang; Voronov, Andriy; Kohut, Ananiy; Gevus, O.; Tokarev, Victor; Voronov, Stanislav (Langmuir, 2006)
We synthesized and characterized novel amphiphilic polyesters with both hydrophilic and hydrophobic functionalities. The polyesters are soluble in organic and aqueous media and reveal the formation of inverse architectures whose behavior could be correlated to their chemical structure. We foresee that the amphiphilic properties of the polyesters reported here are obviously the basis of new architectures both in solution and on the solid surfaces, which could be used in a broad range of applications. The described synthesis of the copolymers is very simple and is based on commercially available products. That makes this approach attractive in various uses.
Keywords: synthesis; characterization; polymer; functionality